Verificação da capacidade fotodegradante de um compósito polimérico com resíduo vítreo visando à inativação de patógenos - Carísio, Pedro de Almeida (2016)
The main means of transmission of infections Related to Health Care (HAIs) occurs by direct contact with the hospital staff, instruments and surfaces containing pathogenic micro-organisms, aerosol droplets from other sick patients or even meals and liquids supplied in hospitals. In areas where there is no control of micro-organisms may arise biofilms, which are formed when microorganisms come together and become a community, they are known for their resistance to antimicrobials and as a major cause of HAIs. By means of photocatalysis, these micro-organisms can be neutralized. Photocatalysis is a process which accelerates the oxidation and reduction reactions of organic substances, among them bacteria. Thus, through the preparation of a polymeric composite with TiO2 and glassy residue content, search attempts to determine a mixture, in an attempt to control the biofilm emergence. The composites were soaked in culture medium containing Staphylococcus aureus bacteria forming biofilms within cell culture plates in 24-well plates, which were subjected in an oven, for a period of 48h under UV illumination and in the dark. Through scanning electron microscopy were generated images of the surfaces of composite in order to investigate whether occured or not the formation of biofilms. Through research, we tested two types of TiO2 (nanocrystals with different sizes) and three variations of the composite content, composed of epoxy resin, TiO2 and glass powder. The result shows that the tested compositions inhibit partly the action of the biofilm.